Disclosure of Shariah related information in Islamic cooperatives: a case study on Baitul Maal Wat Tamwil (BMT) - Mohamad, Rahmawati; Hamdan, Hamdino; Annuar, Hairul Azlan; Abdul Rashid, Hafiz Majdi (Kolej Universiti Islam Selangor (KUIS), 2017)
This study seeks to investigate the disclosure of Shariah related information (SRI) in financial reporting practice of Islamic Cooperative (IC). This paper reports on a case study of three Baitul Maal wat Tamwil (BMT) based organizations that are IC. The financial statements of these organizations are analyzed using a self-constructed index consisting 54 items overall. This study uses annual reports from 2010 to 2013 because they were the most recent data available at the beginning of the study. It found that ICs in Indonesia has used ‘accounting standard for Islamic Financial Institutions’ as standard and there are aspects of Shariah-based disclosure practices for IC that are not adequately implemented in financial practices of IC. This study is expected to contribute to the improvement of ICs level of transparency and financial disclosure. This paper fulfills an identified need to study how Shariah principles can be incorporated into the financial reporting practices of IC that enhance financial disclosure in ICs.